Advances in immunotherapy modalities for atherosclerosis - Meng, Qingwen; Liu, Huajiang; Liu, Jinteng; Pang, Yangyang; Liu, Qibing (Frontiers in Pharmacology, 2023)
Cardiovascular disease(CVD) is one of the leading causes of death worldwide. Atherosclerosis (AS) is a chronic inflammatory disease of the arterial intima caused by an immune response of the body's immune system to endogenous or exogenous antigens, in which both innate immunity and specific immunity play an indispensable role. Recent studies have shown that inducing protective immune responses by certain autoantigens or exogenous antigens can alleviate AS. Some clinical trials have also demonstrated that AS is associated with the presence of immune cells and immune factors in the body. Therefore, immunotherapy is expected to be a new preventive and curative measure for AS. In this review article, we provide a summary overview of recent progress in the research of immune mechanisms of AS and targeted therapeutic pathways.